2018
DOI: 10.1039/c7qo00756f
|View full text |Cite
|
Sign up to set email alerts
|

Where does Au coordinate to N-(2-pyridiyl)benzotriazole: gold-catalyzed chemoselective dehydrogenation and borrowing hydrogen reactions

Abstract: Pyridyltriazole gold(i) complexes proved to be an efficient precatalyst for the most challenging gold-catalyzed borrowing hydrogen reaction and dehydrogenation of alcohols and amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 132 publications
0
13
0
Order By: Relevance
“…Compared with bpy, pyb has the following differences: 1) additional N atoms that can participate in H‐bonding interactions, 2) an additional phenyl group that not only enforces an electron‐rich character of the framework, but also permits participation in stacking interactions, and 3) the pyridine and benzotriazole units are linked by an N atom, which imposes flexibility through the C−N bond and yields different coordination behaviour compared with the rigid C−C‐based bpy ligand. Steel and Richardson, in their pioneering work, found pyb‐based compounds to be more electron‐deficient than those based on bpy; [10] however, the use of well‐characterized pyb‐based complexes in catalysis is almost an unexplored research field [11–14] …”
Section: Introductionmentioning
confidence: 99%
“…Compared with bpy, pyb has the following differences: 1) additional N atoms that can participate in H‐bonding interactions, 2) an additional phenyl group that not only enforces an electron‐rich character of the framework, but also permits participation in stacking interactions, and 3) the pyridine and benzotriazole units are linked by an N atom, which imposes flexibility through the C−N bond and yields different coordination behaviour compared with the rigid C−C‐based bpy ligand. Steel and Richardson, in their pioneering work, found pyb‐based compounds to be more electron‐deficient than those based on bpy; [10] however, the use of well‐characterized pyb‐based complexes in catalysis is almost an unexplored research field [11–14] …”
Section: Introductionmentioning
confidence: 99%
“…In 1981, Grigg and Watanabe reported the first examples of alcohol substitution by N‐nucleophiles in the presence of rhodium, iridium, and ruthenium compounds. Since then, many efficient catalytic methods for the N ‐alkylation of amines as well as the related reactions by activating alcohols were developed using metal catalysts (Ag, Au, Ir, Pd, Re, Ru, Co, Cu, Fe, Mn and Ni), bimetallic catalysts and non‐metal catalysts etc (Scheme a). Most of these catalyst systems needed high temperatures and strong alkalis to work.…”
Section: Methodsmentioning
confidence: 99%
“…A diagnostic copper hydride signal was also observed in solid-state infrared spectroscopy studies, further supporting these findings. In a subsequent article, the authors reported [125] the synthesis of an analogous 0D complex based on gold sources, formulated as [Au I (pbta)(PPh3)]•(CF3SO3) (155). In a similar fashion, 155 was found to be an ideal catalytic precursor in borrowing hydrogen and dehydrogenation reactions of alcohols and amines, resulting in the selective synthesis of substituted amines and ketones as detailed in Scheme 7.…”
Section: N1-substituted Benzotriazolesmentioning
confidence: 99%